Assessment of heavy metals in indoor dust of a university in a tropical environment. Issue 1 (2nd January 2017) - Sulaiman, Fazrul Razman; Bakri, Naqiatul Intan Farhain; Nazmi, Nuraisyah; Latif, Mohd Talib
ABSTRACT: Heavy metal contamination in indoor dust has received much attention, especially in tropical areas. This study measures the concentrations of selected heavy metals in indoor dust collected from three different buildings at Universiti Teknologi MARA (UiTM) Cawangan Pahang, Malaysia. Heavy metal concentrations were, from highest to lowest, Fe > Zn > Cu > Pb > As. The results were dominated by Fe, with a range of 10201–52365 μgg −1 . The metals were primarily from the earth's crust (enrichment factor, EF < 10). However, principle component analysis (PCA) suggested anthropogenic sources of As, Pb, and Zn (Factor 1), and mixed sources of Fe and Cu (Factor 2). The total hazard quotient ( HQ ) was found to be lower than the acceptable level of 1, indicating that exposure to heavy metals in indoor dust poses no noncarcinogenic risks to adults. If metal concentrations increase in the long term, adult exposure in the university environment, especially laboratories, may not be negligible.